ANALISIS KRITIS TERHADAP PEMBANGUNAN DUNIA KETIGA DAN TRANSFORMASI AGRARIA DI INDONESIA - Nur Utaminingsih (WANUA : Jurnal Hubungan Internasional, 2019)
This article discusses a critical investigation of the topic of Third World development and the issue of agrarian transformation in Indonesia. This study uses a qualitative methodology with an in-depth interpretation tracing model of each research component. The Capitalist Block's power / knowledge has been successfully distributed locally in Third World Countries through the Development Project. The local distribution of power / knowledge through the mechanism of creating abnormalities and the formation of the development apparatus plays a role in translating the basic values ​​of capitalism in Indonesia. Agrarian transformation has become one of the social realities of the successful existence of capitalism in the development of Indonesia as a third world country. The meaning of Indonesia as an agrarian country towards agrarian (earth, water, sea, space, and human society, as regulated in UUPA 1960) is increasingly result-oriented through industrialization and commercialization. Agrarian economy morals in Indonesia prioritize control, ownership and use of "land for development." Artikel ini membahas mengenai penelusuran kritis terhadap topik pembangunan Dunia Ketiga dan isu transformasi agraria di Indonesia. Penelitian ini menggunakan metodologi kualitatif dengan model penelusuran interpretasi mendalam dari setiap komponen penelitian. Power/knowledge Blok Kapitalis berhasil didistribusikan secara lokal di Negara Dunia Ketiga melalui Proyek Pembangunan. Distribusi lokal power/knowledge melalui mekanisme penciptaan abnormalitas dan pembentukan aparat pembangunan, berperan menerjemahkan nilai dasar Kapitalisme di Indonesia. Transformasi Agraria menjadi salah satu realitas sosial atas keberhasilan eksistensi Kapitalisme dalam Pembangunan Indonesia sebagai Negara Dunia Ketiga. Pemaknaan Indonesia sebagai negara agraris terhadap agraria (bumi, air, laut, ruang angkasa, dan masyarakat manusia, sebagaimana diatur dalam UUPA 1960) semakin berorientasi hasil melalui industrialisasi dan komersialisasi. Moral ekonomi agraria di Indonesia lebih mengutamakan penguasaan, kepemilikan dan pemanfaatan “tanah untuk Pembangunan.”